2020
DOI: 10.1007/978-3-030-65390-3_46
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Topic and Sentiment Dynamics Due to COVID-19 Pandemic Using Social Media

Abstract: The outbreak of the novel Coronavirus Disease (COVID-19) has greatly influenced people's daily lives across the globe. Emergent measures and policies (e.g., lockdown, social distancing) have been taken by governments to combat this highly infectious disease. However, people's mental health is also at risk due to the long-time strict social isolation rules. Hence, monitoring people's mental health across various events and topics will be extremely necessary for policy makers to make the appropriate decisions. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…Emotional toll can be investigated quantitatively by sentiment analysis, which calculates emotional polarization of text from negative, through neutral, to positive. Three previous studies have attempted to quantify emotional toll using sentiment analysis of social media conversations on COVID-19 [22][23][24]. Counterintuitively, given pandemic subject matter, all three studies of sentiments from COVID-19 conversations on social media showed a higher proportion of positive rather than negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional toll can be investigated quantitatively by sentiment analysis, which calculates emotional polarization of text from negative, through neutral, to positive. Three previous studies have attempted to quantify emotional toll using sentiment analysis of social media conversations on COVID-19 [22][23][24]. Counterintuitively, given pandemic subject matter, all three studies of sentiments from COVID-19 conversations on social media showed a higher proportion of positive rather than negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, et al [ 32 ] also applied topic modeling and opinion analysis to verify whether “Chinese Virus” and “COVID-19” are substitutable. Apart from these studies, several other studies also applied topic modeling to identify different trends in public opinion toward COVID-19 [ 6 , 18 , 22 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Related Workmentioning
confidence: 99%
“…The field of research in crises began to focus on all the information produced in times of crisis, not only determining the type of crisis, but also the results related to it. Therefore, the large amount of social media posts are considered a useful data source to recognize people's mental health during a period of the crisis such as COVID-19 by analyzing the popular topics and their associated sentiments due to the crisis [5]. All research in the field of crises has the main goal of knowing the type of crisis, reaching the injured, and knowing all the required needs.…”
Section: Related Workmentioning
confidence: 99%